2011
DOI: 10.1007/s00240-011-0410-x
|View full text |Cite
|
Sign up to set email alerts
|

Tamsulosin and doxazosin as adjunctive therapy following shock-wave lithotripsy of renal calculi: randomized controlled trial

Abstract: Alpha-blockers have been established as medical expulsive therapy for urolithiasis. We aimed to assess the effect of tamsulosin and doxazosin as adjunctive therapy following SWL for renal calculi. We prospectively included 150 patients who underwent up to four SWL sessions for renal stones from June 2008 to 2009. Patients were randomized into three groups of 50 patients each, group A (phloroglucinol 240 mg daily), group B (tamsulosin 0.4 mg once daily plus phloroglucinol), and group C (doxazosin 4 mg plus phlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
2
12
5
1
Order By: Relevance
“…Contrary to our findings, most of the investigators [12,25,26] have shown that tamsulosin facilitates earlier clearance of stone fragments. We have no proper explanation for this finding.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Contrary to our findings, most of the investigators [12,25,26] have shown that tamsulosin facilitates earlier clearance of stone fragments. We have no proper explanation for this finding.…”
Section: Discussioncontrasting
confidence: 56%
“…The main benefit of adjunctive tamsulosin after renal SWL in our study as well as in most previous studies [13,15,25] is the significant reduction of the post-SWL pain episodes and subsequently the need for additional analgesia. The frequency of pain episodes and cumulative and additional analgesia dosage were consistently lower with adjunctive tamsulosin.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Em um outro estudo randomizado com 150 doentes avaliando os resultados da tamsulosina e da doxazosina após LECO, também não se encontrou vantagens na taxa de doentes livres de cálculos (84% placebo, 92% tamsulosina, 90% doxazosina), porém pacientes em uso de tamsulosina tiveram um significativo menor tempo para expulsão dos cálculos tanto em relação à doxazosina (p=0,026) como em relação ao placebo (p=0,002), e uma menor incidência de episódios de cólicas em relação aos outros dois grupos [79] . Complementando estes estudos, recente metanálise foi publicada avaliando a real eficácia do uso da tamsulosina em pacientes submetidos a LECO [80] .…”
Section: Terapia Expulsiva Medicamentosaunclassified